2008
DOI: 10.1111/j.1523-536x.2008.00225.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of First Childbirth on Changes in Women’s Preference for Mode of Delivery: Follow‐up of a Longitudinal Observational Study

Abstract: A significant proportion of women changed their preferred mode of delivery after their first childbirth. Apart from reducing the number of cesarean sections in nulliparous women, prompt provision of education to women who had complications and investigations into fear factors during vaginal birth might help in reducing women's wish to change to elective cesarean section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
100
3
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(122 citation statements)
references
References 21 publications
10
100
3
9
Order By: Relevance
“…Such agreement between the study findings and Pang et al [48] study which conducted in Hong Kong about impact of first childbirth on delivery mode preference who stated that women were detected to prefer vaginal delivery because of quick postpartum recovery which represented by 27.5% and being natural which represented by 24% of them.…”
Section: Discussionsupporting
confidence: 80%
“…Such agreement between the study findings and Pang et al [48] study which conducted in Hong Kong about impact of first childbirth on delivery mode preference who stated that women were detected to prefer vaginal delivery because of quick postpartum recovery which represented by 27.5% and being natural which represented by 24% of them.…”
Section: Discussionsupporting
confidence: 80%
“…In addition to this, the participants of our study group indicated that the fear of vaginal delivery, bad birth stories and obstetrician's inducement were the main factors behind the increase in the rates of caesarean deliveries. Supporting our study, Pang et al [11] found that the impact of first childbirth affected the decision of next delivery mode.…”
Section: Discussionsupporting
confidence: 72%
“…The primary reasons included fear of vaginal birth, bypassing risks to the fetus from vaginal birth, and protecting the lower genital tract from trauma. Another study found that 23.8% of women who delivered vaginally said they would prefer delivering by cesarean section for their next pregnancy [10]. When asked six months after giving birth, 79% of women (19 of 24) who delivered by cesarean section stated that they would prefer cesarean section again.…”
Section: Discussionmentioning
confidence: 99%